The new bureaucracy : quality assurance and its critics - Travers, Max (Policy, 2007)
This collection adds weight to an emerging argument that suggests that policies in place to make cities better places are inextricably linked to an attempt to civilize, pacify and regulate crime and disorder in urban areas, contributing to a vision of an urban renaissance which is perhaps as much about control as it is about the broader physical and social renewal of our towns and cities. The book has three key themes: the theories, strategies and assumptions underpinning the securing of 'Urban Renaissance'; the agendas of current urban policy in the field of crime control; and, thirdly, the role of communities within these agendas. The book provides focused discussions and engagement with these issues from a range of scholars who examine policy connections that can be traced between social, urban and crime policy and the wider processes of regeneration in British towns and cities. The book also seeks to develop our understanding of policies, theories and practices surrounding contemporary British urban policy where a move from concerns with 'urban renaissance' to those of sustainable communities clearly intersect with issues of community security, policing and disorder. Providing a rare disciplinary crossover between urban studies, criminology and community studies, "Securing an Urban Renaissance" will be essential reading for academics and students in criminology, social policy and human geography concerned with the future of British cities and the political debates shaping the regulation of conduct, crime and disorder in these spaces.